Egg oxidation status, antioxidant enzyme activities, lipid classes, fatty acid composition profile and embryo survival rates during in vitro oocyte ageing in tench Tinca tinca (Linnaeus, 1758). (18th April 2018) - Samarin, Azadeh Mohagheghi; Sampels, Sabine; Krzyskow, Anna; Burkina, Viktoriia; Kristan, Jiri; Gela, David; Flajshans, Martin; Policar, Tomas; Samarin, Azin Mohagheghi
Abstract: The effect of in vitro storage of oocytes on embryos survival rate, egg oxidation status, antioxidant enzyme activities, lipid classes and fatty acid composition profile was investigated in common tench Tinca tinca . In order to identify the role of oxidative stress in the progress of oocyte ageing the levels of thiobarbituric acid reactive substances (TBARS) and carbonyls as indicators of lipid and protein oxidation were measured and the activity of antioxidant enzymes were examined. Stripped ova from six females were stored in cell culture plates at 20°C for up to 10 hr post‐stripping (HPS). The stored ova were fertilized and the embryo survival rates were assessed. The results indicated that tench eggs could be successfully stored in vitro for 4 hr after stripping at 20°C. Superoxide dismutase enzyme activity increased at 6 HPS, whereas glutathione peroxidase and glutathione reductase activities decreased in oocytes during in vitro storage ( p < .05) at 4 and 8 HPSs, respectively. The level of malondialdehyde did not show any significant changes during the progress of oocyte ageing. Carbonyls increased up to 2 HPS and thereafter decreased significantly. However, ova ageing did not affect the main lipid class composition and the fatty acid composition of the eggs. Lower quality eggs exhibited lower levels of cholesterol but higher levels of triacylglycerol.